Ecological problems of the plant cover of the northeastern slope of Great Caucasus (within Azerbaijan) - Nuru Hajiyeva, Gülnar (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Highlight the purpose. Plant cover of our republic, especially forest ecosystems, has lost its original state as a result of the influence of natural and anthropogenic factors. The study of the impact of these factors on biodiversity has been the focus of many experts. The settlement of the studied area since ancient times and the good development of agriculture have caused the degradation and erosion of the forest cover that covers large areas, as well as the vegetation that replaces each other in the altitude zones here. For this reason, the issues of protection and protection of vegetation are distinguished by their relevance. The main goal of our research is to protect the vegetation of forests that have changed their initial state. Objectives. Mountain geosystems of the northeastern slope of the Greater Caucasus are bordered by the Russian Federation to the north, northwest, and west, the Samur-Devachi plain to the east, and the watershed line of the Greater Caucasus Range and Atachay to the south and southeast. Methods. Field studies were organized to solve the issues raised during the research period. Short-term visual observations of the existing geoecological conditions were carried out, from topographic maps and other maps (landscape, vegetation, etc.) of various scales, as well as from 1:25000 scale aerial and space images in the fund of the Institute of Ecology of MAKA, “Google” and “Bing” space images with a resolution of 1 meter in the funds, taken in the visible zone of the spectrum, obtained from various satellites in 2020-2023 and based on the application of SASPlanet, ArcGIS processing programs were used. With the help of these materials, the vegetation degradation and erosion processes of the research area were studied. Results. The northeast part of the Great Caucasus differs from the other mountainous regions for its appropriation features. For a long time appropriation of the investigated zone by the various farming areas caused a serious change in the natural geosystems. Thus, the zones where a hypsometric height of 200-500 m are mainly replaced by agro-complexes, the parts within 500-1800 m turned into a life and rest objects together with the arable and pastures, an irregular use from the summer pastures in cattle-breeding in the zones higher than 1800 m was completed by exposing of the plant cover to transformation. During assimilation, activation of ecological problems like decreased plant productivity, intensification of the erosion process, acceleration of degradation, and so on activates a problem of rational use. Defining importance, sensitiveness of plant cover, and rational use ways as protection, refusal of usage, extensive use of protection, development, extensive use, improvement, and development were determined.